2022
DOI: 10.54755/defendonesia.v6i1.112
|View full text |Cite
|
Sign up to set email alerts
|

Geoekonomi Bank Investasi Infrastruktur Asia (AIIB)

Abstract: Tiongkok sebagai salah satu negara terbesar di dunia dengan populasi terbesar dan negara ekonomi terbesar kedua di dunia. Pada 2013, Presiden Tiongkok Xi Jinping menetapkan jalur perdagangan melalui pembangunan bersama dan kemakmuran dengan meningkatkan kerja sama lintas regional multilateral, yang dapat disebut Jalan Sutra Modern atau One Belt One Road (OBOR). Untuk mendukung OBOR, juga dibentuk Asian Infrastructure Investment Bank (AIIB). Dalam konteks kekuatan ekonomi, AIIB telah berkontribusi dalam meningk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research conducted by the Asian Development Bank (ADB) concluded that the causes of the economic crisis in Asian countries, including Indonesia, are (1) the supervisory mechanism of the Board of Directors and Audit Committee of a company does not function effectively in protecting the interests of shareholders and (2) the management of the company is not professional (Iswardhana, 2022). Thus, the implementation of the GCG concept in Indonesia is expected to improve the professionalism and welfare of shareholders without neglecting the interests of stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by the Asian Development Bank (ADB) concluded that the causes of the economic crisis in Asian countries, including Indonesia, are (1) the supervisory mechanism of the Board of Directors and Audit Committee of a company does not function effectively in protecting the interests of shareholders and (2) the management of the company is not professional (Iswardhana, 2022). Thus, the implementation of the GCG concept in Indonesia is expected to improve the professionalism and welfare of shareholders without neglecting the interests of stakeholders.…”
Section: Introductionmentioning
confidence: 99%